Disaster preparedness in emergency medical service agencies: A systematic review - Mehdi Beyramijam; Mehrdad Farrokhi; Abbas Ebadi; Gholamreza Masoumi; Hamid Reza Khankeh (Journal of Education and Health Promotion, 2021)
The Emergency Medical Services (EMSs) are in the frontline between the health-care systems and people in emergencies and disasters. With the increase in the frequency of natural or man-made disasters around the world, the need for prepared EMS services is increasing. This study aimed to evaluate the current disaster preparedness status of the EMS agencies in the literature and exploring the key preparedness elements and the strategies to improve the EMS disaster preparedness. The electronic database such as PubMed, Web of Science, Scopus, and Google Scholar was searched from 2000 to 2019. The searching keywords included: “EMS,” “Disaster,” “Preparedness,” “Emergency” “Preparedness,” “Disaster Preparedness,” “Readiness,” and the terms related to “disaster types” were used in combination with Boolean operators OR and AND. Out of 1412 articles, 7 articles were included in the review. The most important elements of the EMS disaster preparedness include the size and scope of the incident, surge capacity, planning, communication, training and education, policymaking, financial support, coordination, safety and security, early warning system, disaster response experience, and legal considerations. This systematic review showed that the EMS agencies in the world generally are inadequately prepared for an effective response to major emergencies and disasters. This study provides valuable information to EMS educators, EMS administrators to adopt and perform appropriate activities to improve the EMS disaster preparedness.